PEMBAJAKAN KARYA LAGU MELALUI APLIKASI DI PLAYSTORE MENURUT PERSPEKTIF HAK CIPTA - Aditya Suud (2021)
This study aims to determine and understand how the forms of legal protection for creators and or rights holders related to copyright piracy through applications in Indonesia. Especially for digital computer program copyright works in the form of applications containing electronic documents in the form of songwriting or music belonging to other people which are then published in an application called Playstore. This study uses a juridical-normative research type by applying a statutory approach and a conceptual approach. Collecting data from secondary materials was carried out using literature methods and analyzed using qualitative methods and conducting juridical analysis. The result of this research is that in Indonesia there are no specific rules regarding pirating songs through online media or digital Internet. UU No. 28 of 2014 regarding Copyright has not been able to reach about this. Meanwhile, the information and electronic transactions are regulated in UU No. 19 of 2016 concerning Electronic Information and Transactions. This is also due to the inaccurate concept of regulating piracy in internet or electronic media. The concept needed is to establish a new agency that bridges two different rules, so this will make handling of piracy violations through the Playstore application clearer in the authority to judge these problems.